ANALISIS HADIS WANITA DUPLIKAT SETAN DALAM KITAB SUNAN ABI DAWUD DAN AT-TIRMIZI (KAJIAN SANAD DAN MATAN) - Fadhilah Is (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
Duplicate female hadith in sunan Abu Dawud is found in the Kitab an-Nikah, chapter Ma Yu'mar bihi min Gadhi al-Bashar, hadith number 2151. And in the book Sunan at-Tirmizi in the chapter ar-Rajul Yaraa al-Mar'ah wa Tu'jibuhu, hadith number 1158. Both of these traditions have met the criteria of the valid hadith. This hadith (female duplicate devil) is not understood in terms of hadith texts, this similarity is not physical and external appearance because the physical and outer appearance of the woman is far different from the physical and demonic appearance. The woman's physical and appearance are very attractive, while the physical and demonic features are very disgusting. But it lies in the inner attraction that exists in the woman who is being wary through whispers, persuasions and demonic seduction to men.